Metabolomics profiling reveals the detoxification and tolerance behavior of two bread wheat (Triticum aestivum L.) varieties under arsenate stress - Muhammad Saeed; Umar Masood Quraishi; Ghazala Mustafa; Abida Farooqi; Maria Greger; Riffat Naseem Malik (Food Chemistry, 2024)

Removal of PFAS from water by aquatic plants - Maria Greger; Tommy Landberg (Journal of Environmental Management, 2024)

Phenomic profiling to reveal tolerance mechanisms and regulation of ascorbate–glutathione cycle in wheat varieties (Triticum aestivum L.) under arsenic stress - Muhammad Saeed; Umar Masood Quraishi; Tommy Landberg; Maria Greger; Riffat Naseem Malik (Environmental Geochemistry and Health, 2024)

Differences in Metal Accumulation from Stormwater by Three Plant Species Growing in Floating Treatment Wetlands in a Cold Climate - Emre Boynukisa; Maria Schück; Maria Greger (Water, Air, & Soil Pollution, 2023)
Stormwater is a source of pollutants in urban areas and should be treated to prevent negative environmental effects. A newer technique uses floating rafts with plants, called floating treatment wetlands (FTWs), which are placed in the polluted water. Few earlier studies have examined heavy metal removal by FTWs, and none has examined stormwater in cold climates. This study therefore aimed to determine whether plants growing in FTWs could accumulate heavy metals from stormwater ponds in a cold climate. This study examined the abilities of three native wetland species (i.e., Carex riparia , C. pseudocyperus , and Phalaris arundinacea ) to accumulate Cd, Cu, Pb, and Zn. The plants were planted on FTWs, which were placed in two stormwater ponds in Stockholm, Sweden, for 12 weeks. Phalaris arundinacea accumulated more Cd, Cu, and Zn than did the Carex species, and C. pseudocyperus accumulated less Pb than did the other species during the experimental period. In most cases, the roots had higher metal concentrations than did the shoots. Carex pseudocyperus had smaller differences between shoot and root metal contents, whereas P. arundinacea had higher Cd and Cu contents and lower Zn contents in its roots than in its shoots. The metal content in the plants increased with higher biomass. The plants that grew in the stormwater pond with a higher Zn concentration had a higher Zn tissue concentration and total Zn content per plant after treatment. This study shows that wetland plants growing on FTWs can accumulate metals from stormwater ponds in a cold climate. Phalaris arundinacea appears to be a good candidate for metal removal use in FTWs. Furthermore, high plant biomass positively affects the metal uptake, meaning that good growing conditions could be essential for metal removal.

Salinity and temperature influence removal levels of heavy metals and chloride from water by wetland plants - Maria Schück; Maria Greger (Environmental Science and Pollution Research, 2023)
Stormwater with low temperatures and elevated salinity, common in areas where deicing salt is used, might affect the removal of heavy metals by plants in stormwater treatment systems such as floating treatment wetlands. This short-term study evaluated the effects of combinations of temperature (5, 15, and 25 °C) and salinity (0, 100, and 1000 mg NaCl L −1 ) on the removal of Cd, Cu, Pb, and Zn (1.2, 68.5, 78.4, and 559 μg L −1 ) and Cl − (0, 60, and 600 mg Cl − L −1 ) by Carex pseudocyperus , C. riparia , and Phalaris arundinacea. These species had previously been identified as suitable candidates for floating treatment wetland applications. The study found high removal capacity in all treatment combinations, especially for Pb and Cu. However, low temperatures decreased the removal of all heavy metals, and increased salinity decreased the removal of Cd and Pb but had no effect on the removal of Zn or Cu. No interactions were found between the effects of salinity and of temperature. Carex pseudocyperus best removed Cu and Pb, whereas P. arundinacea best removed Cd, Zu, and Cl − . The removal efficacy for metals was generally high, with elevated salinity and low temperatures having small impacts. The findings indicate that efficient heavy metal removal can also be expected in cold saline waters if the right plant species are used.

Population genomic, olfactory, dietary, and gut microbiota analyses demonstrate the unique evolutionary trajectory of feral pigs - Simona Petrelli; Maria Buglione; Valeria Maselli; Claudia Troiano; Greger Larson; Laurent Frantz; Aurelie Manin; Ezio Ricca; Loredana Baccigalupi; Dominic Wright; Christian Pietri; Domenico Fulgione (Molecular Ecology, 2022)
Domestication is an intriguing evolutionary process. Many domestic populations are subjected to strong human‐mediated selection, and when some individuals return to the wild, they are again subjected to selective forces associated with new environments. Generally, these feral populations evolve into something different from their wild predecessors and their members typically possess a combination of both wild and human selected traits. Feralisation can manifest in different forms on a spectrum from a wild to a domestic phenotype. This depends on how the rewilded domesticated populations can readapt to natural environments based on how much potential and flexibility the ancestral genome retains after its domestication signature. Whether feralisation leads to the evolution of new traits that do not exist in the wild or to convergence with wild forms, however, remains unclear. To address this question, we performed population genomic, olfactory, dietary, and gut microbiota analyses on different populations of Sus scrofa (wild boar, hybrid, feral and several domestic pig breeds). Porcine single nucleotide polymorphisms (SNPs) analysis shows that the feral population represents a cluster distinctly separate from all others. Its members display signatures of past artificial selection, as demonstrated by values of F ST in specific regions of the genome and bottleneck signature, such as the number and length of runs of homozygosity. Generalised F ST values, reacquired olfactory abilities, diet, and gut microbiota variation show current responses to natural selection. Our results suggest that feral pigs are an independent evolutionary unit which can persist so long as levels of human intervention remain unchanged.

Arsenic concentrations in local aromatic and high-yielding hybrid rice cultivars and the potential health risk: a study in an arsenic hotspot - Arifin Sandhi; Maria Greger; Tommy Landberg; Gunnar Jacks; Prosun Bhattacharya (Environmental Monitoring and Assessment, 2017)

Changes in pH and organic acids in mucilage of Eriophorum angustifolium roots after exposure to elevated concentrations of toxic elements - M. Tariq Javed; Eva Stoltz; Sylvia Lindberg; Maria Greger (Environmental Science and Pollution Research, 2013)

Stabilization of Mine Tailings Using Fly Ash and Sewage Sludge Planted with Phalaris arundinacea L. - Clara Neuschütz; Maria Greger (Water, Air, & Soil Pollution, 2010)

Role of rhizosphere mechanisms in Cd uptake by various wheat cultivars - Maria Greger; Tommy Landberg (Plant and Soil, 2008)

Release of metals and arsenic from various mine tailings by Eriophorum angustifolium - Eva Stoltz; Maria Greger (Plant and Soil, 2006)

Effects of Different Wetland Plant Species on Fresh Unweathered Sulphidic Mine Tailings - Eva Stoltz; Maria Greger (Plant and Soil, 2005)

Changes in Hg fractionation in soil induced by willow - Yaodong Wang; Clotilde Stauffer; Catherine Keller; Maria Greger (Plant and Soil, 2005)

A new method to detect cadmium uptake in protoplasts - Sylvia Lindberg; Tommy Landberg; Maria Greger (Planta, 2004)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)